2002
DOI: 10.1523/jneurosci.22-02-j0006.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Ascorbate Release in the Striatum of Behaving Mice Expressing the Huntington's Disease Gene

Abstract: The extracellular fluid of the striatum contains a high level of ascorbate, an antioxidant vitamin known to play a key role in behavioral activation. We assessed the extracellular dynamics of ascorbate in R6/2 mice engineered to express the gene for Huntington's disease (HD), an autosomal dominant condition characterized by the loss of striatal neurons. Slow-scan voltammetry was used to measure striatal ascorbate during anesthesia and subsequent behavioral recovery. Although both the HD mice and their litterma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
61
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 31 publications
17
61
6
Order By: Relevance
“…Although the decrease in striatal AA release upon behavioral activation observed in KI males was less prominent and more variable than that previously described in male R6/2 mice, the deficit in male KI mice, ~20-40% was similar to that of R6/2 mice [26]. This deficit suggests that male HD mice may be more susceptible to oxidative stress in the striatum.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Although the decrease in striatal AA release upon behavioral activation observed in KI males was less prominent and more variable than that previously described in male R6/2 mice, the deficit in male KI mice, ~20-40% was similar to that of R6/2 mice [26]. This deficit suggests that male HD mice may be more susceptible to oxidative stress in the striatum.…”
Section: Discussionmentioning
confidence: 47%
“…On the day of recording, both the working electrode and an Ag/AgCl reference electrode were fitted into separate microdrives, which were designed to mate with the head-mounted hubs [26]. After the microdrives were prepared, the mouse was lightly anesthetized with chloropent (0.2ml/100g, i.p.)…”
Section: Voltammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular ascorbate is reduced in the striatum of R6/2 mice. 142 When animals were treated with intraperitoneal injections of ascorbate, 4 days per week, from 6 -10 weeks of age, there were significant reductions in stereotypic grooming and an increase in cognitive performance was detected. Unfortunately, the authors did not evaluate whether ascorbate administration had any effects on life span, aggregate formation, and neuropathology of R6/2 mice.…”
Section: The Effects Of Other Drugs In R6 Micementioning
confidence: 99%
“…Therefore, one can speculate that the primary effect of α-lipoic acid may not necessarily be at the level of the CNS. It has been shown that the levels of the antioxidant ascorbate are reduced in the striatal extracellular fluid of R6/ 2 mice during periods of behavioral activation (Rebec et al, 2002). I.p.…”
Section: Antioxidantsmentioning
confidence: 99%